The Rationality of the Max Weber Bureaucracy Model in the Modrenization of the Public Services Bureaucracy of the Industrial Era 4.0 (Case Study of Medan City E-KTP Services) - Saputra, Agung; Mahardika, Ananda; Izharsyah, Jehan Ridho (Budapest International Research and Critics University, 2021)
Bureaucracy is the most important part in the course of a government. Like the Max Weber Model which still exists in the bureaucratic system in Indonesia. This can be seen how the Weber Model is still an option in implementing a powerful bureaucracy from time to time. However, is this model still a bullet and a selling point that has a high character in creating good governance as described by de Gay who in his bureaucratic theory states that the most important thing in bureaucracy and a service is work ethic. This research is to see the rationality of Max Weber's Bureaucracy Model in the Modernization of Public Service Bureaucracy in the Industrial Era 4.0 (Case Study of Medan City E-KTP Service). This study uses a qualitative descriptive approach with strengthening the literature to analyze cases and conduct discussions. The results of this study are first, the Medan Department of Population and Civil Registration implementation still mostly uses administration and written documents and this tends to make the office (bureau) the center of a modern organization, secondly, staff members are personally free, in the sense that they only carry out their duties. This impersonal task according to their position looks stiff and still exists in some staff, third, the separation of powers also still needs to be considered because it can also have positive and negative effects with the quality of performance and limited employee skills and amateur administration is still in the Department of Population and Civil Registration Medan. Recommendations from this research Department of Population and Civil Registration Medan need to develop and strengthen services through digitization, the concept of team work needs to be strengthened and it needs to be strengthened and developed the competence of staff expertise with soft skills to reduce the meaning of amateur administration using honorary staff